Leite derramado: uma análise de marketing social para os bancos de leite humano - Alves, Joice dos Santos (2020)
Studies on human milk donation associated with the knowledge of social marketing theory and action enrich the field of study, making it possible for the institutions involved to progress through the information obtained. Thus, the general objective of this work is to analyze how the Human Milk Banks act in favor of the donation of human milk from the perspective of the agents involved. For this, the research had a qualitative and exploratory approach, being divided into field research and documentary research. The interviewed subjects were human milk donors, those responsible for recipients, non-donor mothers and professionals from the HMB, totaling 22 interviews. In general, it was identified that the main actions taken by the professionals of the HMB suffer structural difficulties, such as partnerships with primary care and financial and material resources, interfering in the dissemination of information about the donation. This all causes disparities between the numbers of donors and recipients, guided by the lack of knowledge about the milk donation process. These circumstances indicate that it is essential to reformulate the information system on human milk donation, starting with the implementation of the topic on the women's health and family health agenda, considering that the results point to the need to disseminate information even in the pre -natural, so that women can absorb information properly, generating awareness and facilitating adherence.